2016
DOI: 10.1002/adsc.201500844
|View full text |Cite
|
Sign up to set email alerts
|

Miyaura Borylation and One‐Pot Two‐Step Homocoupling of Aryl Chlorides and Bromides under Solvent‐Free Conditions

Abstract: Solvent‐free protocols for Miyaura borylation and the one‐pot, two‐step homocoupling of aryl halides are reported for the first time. Bis(dibenzylideneacetone)palladium(0) [Pd(dba)2] is an optimal source of palladium for Miyaura borylation, while for one‐pot two‐step homocoupling palladium(II) acetate [Pd(OAc)2] gives highest yields. Aryl bromides are coupled most efficiently using the DPEphos ligand. Chlorides are coupled using XPhos. The developed protocols are robust, versatile and easily reproducible on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…To this end, a handful of research groups have investigated the scope of one-pot synthesis of biaryls in terms of catalyst, base and aryl halides. [17][18][19][20][21][22] Early discoveries have shown that bis(pinacolato) diboron could be used as a condensation reagent for the onepot synthesis of low to moderate molecular weight poly(arylene)s, 23 and that certain bases such as K 2 CO 3 may lead to oligomer formation in biaryl systems. 24 In 2009, Reynolds et al revisited this synthetic pathway and specically studied the effect of CsF on the homopolymerization of uorenes.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, a handful of research groups have investigated the scope of one-pot synthesis of biaryls in terms of catalyst, base and aryl halides. [17][18][19][20][21][22] Early discoveries have shown that bis(pinacolato) diboron could be used as a condensation reagent for the onepot synthesis of low to moderate molecular weight poly(arylene)s, 23 and that certain bases such as K 2 CO 3 may lead to oligomer formation in biaryl systems. 24 In 2009, Reynolds et al revisited this synthetic pathway and specically studied the effect of CsF on the homopolymerization of uorenes.…”
Section: Introductionmentioning
confidence: 99%
“…PdCl 2 (PPh 3 ) 2 [25, 42] exhibited low activity for borylation of 4-chloroanisole (Table 1, entry 3). Catalytic systems Pd(PPh 3 ) 4 /PCy 3 [43], Pd 2 dba 3 /PCy 3 [43, 44], Pd 2 dba 3 /XPhos [28, 45], Pd 2 dba 3 /SPhos [28, 45], Pd(OAc) 2 /PCy 3 [43, 46], Pd(OAc) 2 /XPhos [45, 47] gave moderate to good yields (Table 1, entries 2 and 6–10). Then we tested room temperature for the reaction of 4-chloroanisole.…”
Section: Resultsmentioning
confidence: 99%
“…By taking this challenge, an initial synthetic scheme has been introduced upon the basis of several study (Scheme ) . The reaction involves Suzuki‐Miyaura borylation by using bispinacolatodiboron (B 2 Pin 2 ) wherein homo‐coupling products are obtained as side products along with major borylated products in the presence of sodium acetate as a base.…”
Section: Methodsmentioning
confidence: 99%
“…By taking this challenge, an initial synthetic scheme has been introduced upon the basis of several study (Scheme 1). [9][10][11][12][13][14][15] The reaction involves Suzuki-Miyaura borylation by using bispinacolatodiboron (B 2 Pin 2 ) wherein homo-coupling products are obtained as side products along with major borylated products in the presence of sodium acetate as a base. It is well known that Suzuki-Miyaura borylation reactions have higher functional group tolerance and that emerged as a positive point in this specific case when compared to oxidative cross coupling reactions requiring directing groups.…”
mentioning
confidence: 99%